2007
DOI: 10.1007/s11745-007-3095-8
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Health Effects of Individual trans Fatty Acid Isomers

Abstract: There are multiple adverse effects of trans fatty acids (TFA) that are produced by partial hydrogenation (i.e., manufactured TFA), on CVD, blood lipids, inflammation, oxidative stress, endothelial health, body weight, insulin sensitivity, and cancer. It is not yet clear how specific TFA isomers vary in their biological activity and mechanisms of action. There is evidence of health benefits on some of the endpoints that have been studied for some animal TFA isomers, such as conjugated linoleic acid; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
115
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 104 publications
0
115
1
4
Order By: Relevance
“…Moreover, vaccenic acid is a precursor of CLA and dairy is the main dietary source of CLA, which has been shown to reduce body weight and fat depositions in several animal studies. 5,6 In agreement with this, a cross-sectional study of TFA in adipose tissue suggested that individual TFA isomers may have divergent effects on adiposity. 33 For fatty acids not synthesised endogenously in humans, such as TFA, the proportions in adipose tissue tend to correlate well with dietary intake and reflect the dietary intake of fatty acids during the previous couple of years.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Moreover, vaccenic acid is a precursor of CLA and dairy is the main dietary source of CLA, which has been shown to reduce body weight and fat depositions in several animal studies. 5,6 In agreement with this, a cross-sectional study of TFA in adipose tissue suggested that individual TFA isomers may have divergent effects on adiposity. 33 For fatty acids not synthesised endogenously in humans, such as TFA, the proportions in adipose tissue tend to correlate well with dietary intake and reflect the dietary intake of fatty acids during the previous couple of years.…”
Section: Discussionmentioning
confidence: 57%
“…3,4 Several animal studies have found that feeding CLA reduces body weight and fat depositions, but the results from human studies have been inconsistent. 5,6 Studies have suggested that industrial TFA (I-TFA) and R-TFA may elicit different biological effects. 7 It has been hypothesised that R-TFA, or some specific TFA isomers, may elicit health benefits, but the evidence is weak and more studies are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of iTFA has adverse effects on cardiovascular health by altering blood lipid profile (increase of total to HDL cholesterol ratio, increase in LDL-cholesterol, decrease in HDL-cholesterol), by modifying apolipoprotein levels, and by promoting systemic inflammation as well as endothelial dysfunction [4][5][6][7][8][9][10]. The various isomers of TFA may have different biological and physiological effects as a function of the length of the carbon chain, the number and the position of the carbon-carbon double bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, dietary fatty acids represent key factors having a significant impact on health, especially on CVD. Specific effects of clusters or isolated fatty acids have been extensively studied, with a particular attention paid to saturated fatty acids (SFAs) and trans fatty acids (TFAs) (Katan et al, 1995;Hu et al, 1997;Ascherio et al, 1999;Gebauer et al, 2007). Reports from different health authorities and agencies recommend a reduction of SFA and TFA intake (Stender and Dyerberg, 2003;Scientific Panel on Dietetic Products, 2004;Afssa, 2005).…”
Section: Introductionmentioning
confidence: 99%